A comprehensive analysis of impacts of socio-economic development and land use on river water quality in a megacity-region: a case study. (23rd February 2023) - Zhu, Liying; Chen, Yuanyuan; Wang, Yawei; Wei, Yuansong; Zheng, Hua; Zhang, Yuxin
Abstract: A comprehensive analysis of impacts of socio-economic development and land use on water quality is very useful for better planning and management of river basins by government. In this study, the North Canal River through a megacity-region of Beijing-Tianjin-Hebei Province in China was chosen to quantify impact of 10 socio-economic factors and 6 land use types on water quality in the watershed. The principal component regression (PCR) method was thus applied in this study to quantify effects of socio-economic development and land use types on river water quality through overcoming multicollinearity problems among influencing factors. Results showed that the water quality in the North Canal River improved significantly from serious pollution. Compared with 2010, the annual average pollution index (PI) of COD, NH3 –N, TN, and TP decreased significantly in 2018, especially the PI of NH3 –N decreased the most, from 8.62 in 2010 to <1 in 2018, implying that the concentration of NH3 –N basically met the water quality assessment standard in 2018. The major water pollutant in the basin had shifted from NH3 –N in 2010 to TN in 2018. The absolute impact coefficients of industrial restructuring, population density, upgraded municipal sewage treatment requirements (including sewage treatment rate and discharge standards of water pollutants for municipal WWTPs), and urbanization rate with COD, NH3 –N and TP were higher than those of other factors, indicating that the impact of socio-economic factors on water quality was more significant than that of land use types, and the socio-economic factors may offset or alter the impact of land use on river water quality in areas disturbed by human activities.